2013
DOI: 10.1093/eurjhf/hft104
|View full text |Cite
|
Sign up to set email alerts
|

Coronary microvascular dysfunction is an early feature of cardiac involvement in patients with Anderson–Fabry disease

Abstract: AimsMale patients with Anderson-Fabry disease (AFD) often exhibit cardiac involvement, characterized by LV hypertrophy (LVH), associated with severe coronary microvascular dysfunction (CMD). Whether CMD is present in patients without LVH, particularly when female, remains unresolved. The aim of the study was to investigate the presence of CMD by positron emission tomography (PET) in AFD patients of both genders, with and without evidence of LVH. Methods and resultsWe assessed myocardial blood flow following di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 35 publications
1
42
0
5
Order By: Relevance
“…Rest MBF, peak stress MBF and CFR per unit LV mass was significantly lower in the amyloid compared to the LVH group (Figure 2), suggesting differences independent of LV mass. The myocardial extracellular volume fraction may be expanded and the functioning myocardial mass as estimated by echocardiography may thus be lower in the amyloid compared to control subjects (22). Hence, we performed sensitivity analysis assuming a functioning myocardial mass of 0.50 and 0.75; the stress MBF was significantly lower at LV mass 0.75 (trend to lower stress MBF at LV mass 0.5) and CFR values remain significantly lower in the amyloid subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rest MBF, peak stress MBF and CFR per unit LV mass was significantly lower in the amyloid compared to the LVH group (Figure 2), suggesting differences independent of LV mass. The myocardial extracellular volume fraction may be expanded and the functioning myocardial mass as estimated by echocardiography may thus be lower in the amyloid compared to control subjects (22). Hence, we performed sensitivity analysis assuming a functioning myocardial mass of 0.50 and 0.75; the stress MBF was significantly lower at LV mass 0.75 (trend to lower stress MBF at LV mass 0.5) and CFR values remain significantly lower in the amyloid subjects.…”
Section: Resultsmentioning
confidence: 99%
“…The magnitude of the microvascular dysfunction in our amyloid patients is not only more severe than those seen in hypertensive disease, but are also more severe to previously reported data in dilated cardiomyopathy (21) and in Fabry’s disease. (20,22)…”
Section: Discussionmentioning
confidence: 99%
“…A seminal cardiac pathology in Fabry’s cardiomyopathy is globotriaosylceramide deposition in myocytes with vacuolization[32]. These deposits may activate a variety of signaling pathways leading to hypertrophy, apoptosis, necrosis and fibrosis, which increase coronary vascular resistance, myocardial oxygen demand, and cause CMD[33]. CMD has the potential to cause myocardial fibrosis in Fabry’s Disease[34].…”
Section: Fabry’s Diseasementioning
confidence: 99%
“…CMD has the potential to cause myocardial fibrosis in Fabry’s Disease[34]. Although CMD is more severe among those with LV hypertrophy, it is also seen in women and among individuals without LV hypertrophy[33]; these authors thus, propose that in addition to capillary rarefaction, and microvascular compression, pathologies related to LV hypertrophy, endothelial dysfunction from the storage of glycosphingolipids, dysregulation of the nitric oxide pathway, and microvascular remodeling may contribute to CMD in Fabry’s disease[33]. Also, on intravascular ultrasound imaging patients with Fabry’s disease demonstrate diffuse hypoechoic coronary plaques with greater lipid cores compared to control individuals[35].…”
Section: Fabry’s Diseasementioning
confidence: 99%
“…However, Tomberli et al demonstrated that the microvascular coronary involvement could be present even without LVH, suggesting that it could be an early damage of the disease. 19 The population included in this study consisted of 30 patients with FDconfirmed diagnosis, where 12 (40%) of them were male. The analysis of the mutations showed that 10 were related to the disease classic phenotype, whereas the remaining (p.Asn215-Ser) were associated with a milder form of the disease of later onset (fourth to fifth decade).…”
Section: Coronary Reserve In Fdmentioning
confidence: 99%